Effect of Irrigation System and Irrigation Interval on Seed Yield and Water Productivity of two Soybeans (Glycine max L. Merr.) Cultivars under Drip and Furrow Irrigation in Eastern Sudan (University of Khartoum Journal of Agricultural Sciences, 2022)
Water stress is one of the limiting factors of soybean yield in eastern Sudan. The objective of this study was to obtain basic information on soybean cultivation using two irrigation systems in eastern Sudan. This study examined the leaf area index, yield and irrigation water productivity (IWP) response using two soybean cultivars: Sudan1 (V1) and Sudan2 (V2) under drip (DS1) and furrow (DS2) irrigation systems. The experiment was carried out in the summer seasons of 2016 and 2017. Three irrigation intervals, every 4, 8 and 12 days designated as W1, W2 and W3, respectively, were used. A randomized complete block design was used as strip-split plot arrangement with three replications. The data were statistically analyzed using STATISTICS 10; mean separation was computed using LSD. The results showed that cultivar Sudan1 gave higher leaf area index values under four days irrigation interval particularly with furrow irrigation system. Four days irrigation interval treatment increased seeds yield by more than 2.5 % relative to 8 days irrigation interval and 34 % relative to 12 days irrigation interval, as average for both seasons. Drip irrigation system significantly (P ≤ 0.05) increased IWP compared to furrow irrigation system. Highest water productivity was obtained under four days irrigation interval. Eight days irrigation interval significantly (P ≤ 0.05) inhibited the positive effect of irrigation system on seed yield and IWP. The study concludes that IWP for drip irrigation, in both seasons, was 20.5 % higher than furrow irrigation. However, mean seed yield for furrow system, in both seasons, was 25.6% higher than drip irrigation system.